Contemporary Fiqh Learning Strategies in Addressing Religious Dilemmas of Adolescents in the Social Media Era - Tsaaniyatush Shoolihah Fauzan (Konsultan Jurnal Ilmiah Indonesia, 2025)
This study examines contemporary fiqh learning strategies in responding to religious dilemmas faced by adolescents in the social media era. Social media has transformed how adolescents access religious information, often presenting challenges such as unverified content, diverse interpretations, and social pressure. Through a descriptive qualitative approach, this research identifies four main aspects: characteristics of adolescent religious dilemmas on social media, relevance of contemporary fiqh learning, effective learning strategies, and their implementation in Islamic education contexts. The findings indicate that contemporary fiqh learning needs to integrate digital literacy, interactive learning methods, contextual approaches, and critical guidance to help adolescents navigate the complexity of religious information on social media. This study recommends developing a fiqh curriculum responsive to digital dynamics and enhancing educators' competencies in utilizing technology for meaningful learning.